Alleviation of Ulcerative Colitis Potentially through th1/th2 Cytokine Balance by a Mixture of Rg3-enriched Korean Red Ginseng Extract and Persicaria tinctoria - Evelyn Saba; Yuan Yee Lee; Man Hee Rhee; Sung-Dae Kim (Molecules, 2020)
Ginseng is a vastly used herbal supplement in Southeast Asian countries. Red ginseng extract enriched with Rg3 (Rg3-RGE) is a formula that has been extensively studied owing to its various biological properties. Persicaria tinctoria (PT), belonging to the Polygonaceae family, has also been reported for its anti-inflammatory properties. Ulcerative colitis (UC) is inflammation of the large intestine, particularly in the colon. This disease is increasingly common and has high probability of relapse. We investigated, separately and in combination, the effects of Rg3-RGE and PT using murine exemplary of UC induced by DSS (Dextran Sulfate Sodium). For in vitro and in vivo experiments, nitric oxide assay, qRT-Polymerase Chain Reaction (PCR), Western blot, ulcerative colitis introduced by DSS, Enzyme Linked Immunosorbent Assay (ELISA), and flow cytometry analysis were performed. The results obtained demonstrate that treatment with Rg3-RGE + PT showed synergism to suppress inflammation (in vitro) in RAW 264.7 cells via mitogen-activated protein kinase and nuclear factor κB pathways. Moreover, in C57BL/6 mice, this mixture exhibits strong anti-inflammatory effects in restoring colon length, histopathological damage, pro-inflammatory mediators, and cytokines amount, and decreasing levels of NLRP3 inflammasome (in vivo). Our results recommend that this mixture can be used for the prevention of UC as a prophylactic/therapeutic supplement.